Islamic Values in Navigating Identity Crisis: A Psycho-Spiritual Reading of Dazai Osamu’s No Longer Human - Muhammad Ulul Albab; Lora Hilal Fikri; Muhammad Imdadur Rohman; Aan Miftakhul Fawaid; Abdul Chamid Asy’ari; M. Haris Zainullah (JURNAL ISLAM NUSANTARA, 2025)
This study aims to examine how Islamic values function as psycho-spiritual resources for addressing adolescent identity crises as represented in the novel Rejected as Human. Contemporary adolescents increasingly experience identity fragmentation amid rapid globalization, digital culture, and weakened moral-spiritual anchors. This condition contributes to moral disorientation and social alienation, indicating the urgency of value-based approaches to identity reconstruction. This research employs a descriptive qualitative design grounded in library research and textual analysis. Data were derived from close readings of the novel and thematically analyzed in dialogue with Islamic ethical frameworks. The findings show that identity crisis in the narrative manifests as existential emptiness, moral disorientation, and relational disconnection. Islamic values provide integrative resources for reconstructing meaning and moral agency through spiritual orientation, ethical discipline, social solidarity, and inner purification. Literary narratives function as reflective media that enable experiential moral learning and psycho-spiritual awareness. The application of religious moderation supports balanced spirituality that integrates devotion with social responsibility in plural contexts. Core values operate synergistically to strengthen inner stability, ethical clarity, and relational responsibility. The study contributes an integrative framework linking Islamic moral philosophy with literary analysis for identity reconstruction. Future research is recommended to extend comparative texts and empirical applications in educational settings.